Jugend - Lebenswelt - Bildung Perspektiven für die Jugendforschung in Österreich - Berger, Fred; Guerrini, Flavia; Bütow, Birgit; Fennes, Helmut; Lauermann, Karin; Sting, Stephan; Waechter, Natalia (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2022)
The book gives an overview of the Austrian history in youth research, includes major contributions on current empirical and theoretical analyses and offers new perspectives on youth research in Austria. It covers topics such as education, transitions, health, migration, participation, discrimination, media, values, and youth work. The target groups are researchers as well as politicians and practitioners in the field of social work.